Whole-genome association studies: practical advice and considerations - Weale, Mike (Henry Stewart Talks, 2007)
What are whole-genome (genome-wide) association studies and why do them?, Steps in WGA study, HIV setpoint, Phenotype definition, Setpoint, Whole genome genotyping panels, PLINK, Cryptic population stratification, PCA and EIGENSTRAT, SNP-by-SNP analysis, Multiple testing approaches, Bonferroni method, Q-Q (quantile-quantile) plot, False discovery rate, Permutation, Outright hits, Pool of hits, Bayesian alternatives, Bayes factor, Bayesian false discovery probability (BFDP)